Anticipating white‐nose syndrome in the Southern Hemisphere: Widespread conditions favourable to Pseudogymnoascus destructans pose a serious risk to Australia's bat fauna. (31st October 2019) - Turbill, Christopher; Welbergen, Justin A.
Abstract: There is a serious concern that white‐nose syndrome (WNS), a fungal disease causing severe population declines in North American bats, could soon threaten bats on the Australian continent. Despite an 'almost certain' risk of incursion within the next ten years, and high virulence in naïve bat populations, we remain uncertain about the vulnerability of Australian bats to WNS. In this study, we intersected occurrences for the 27 cave roosting bat species in Australia with interpolated data on mean annual surface temperature, which provides a proxy for thermal conditions within a cave and hence its suitability for growth by the fungal pathogen Pseudogymnoascus destructans . Our analysis identifies favourable roost thermal conditions within 30–100% of the ranges of eight bat species across south‐eastern Australia, including for seven species already listed as threatened with extinction. These results demonstrate the potential for widespread exposure to P. destructans and suggest that WNS could pose a serious risk to the conservation of Australia's bat fauna. The impacts of exposure to P. destructans will depend, however, on the sensitivity of bats to developing WNS, and a more comprehensive vulnerability assessment is currently prevented by a lack of information on the hibernation biology of Australian bats. Thus, given the clear potential for widespread exposure of Australia's bats to P. destructans demonstrated by our study, two specific policy actions seem justified: (i) urgent implementation of border controls that identify and decontaminate cave‐associated fomites and (ii) dedicated funding to enable research on key aspects of bat winter behaviour and hibernation physiology. Further, as accidental translocation of this fungus could also pose a risk to other naïve bat faunas in cooler regions of southern Africa and South America, we argue that a proactive, globally coordinated approach is required to understand and mitigate the potential impacts of WNS spreading to Southern Hemisphere bats.